Controle para protótipos registrados com laser de femtosegundos - Fiorin, Rodrigo (2013)
One of the problems of manufacturing prototypes of photonic devices that control the various parameters of construction. The utilization of the femtosecond laser for the fabrication of optical devices is increasingly common due to their qualities and properties. With the utilization of the instructions for programming and femtosecond laser was possible alteration of the index of refraction of the substrates of soda-lime and fused silica, making viable guiding in planar structures. With these guiding structures properly produced and characterized, it was possible to build a directional coupler, showing the possibility of control for the manufacture of various devices.